Markers of the pathological course of perinatal period in children with echogenic intracardiac focus - E.I. Malinina; O.A. Rychkova; T.V. Chernysheva (LCC «Medicine-Inform», 2020)
E.I. Malinina1, O.A. Rychkova1, T.V. Chernysheva2 1Tyumen State Medical University, Tyumen, Russian Federation 2Tyumen Cardiology Research Center - branch of Tomsk National Research Medical Center of the Russian Academy of Sciences, Tyumen, Russian Federation Aim: to describe the course of perinatal period in children with echogenic intracardiac focus (EIF) diagnosed in the antenatal period. Patients and Methods: in this case-control study, the groups were similar in age, obstetric history, and somatic status of mothers. Group 1 included 214 pregnant women whose fetus (newborn later) was diagnosed with EIF. Inclusion criteria were an echoic focus within the fetal heart (by prenatal ultrasound) as well as pregnancy follow-up and childbirth in the Perinatal Center of Tyumen city. Group 2 included 107 pregnant women whose fetus (newborn later) had no this sonographic sign. Retrospective analysis of the course of antenatal and intranatal periods of newborns with EIF was performed. The course of early neonatal period was described. Placental histology (n = 69) and autopsies of perinatal losses (n=12) were discussed. Results: it was demonstrated that EIFs identified for the first time after 20 weeks of gestation persist after delivery much more common (p<0.01) when associated with impaired fetoplacental circulation. More than 50% of mothers (p<0.01) whose fetuses were diagnosed with EIF had pathological pregnancy. During the delivery, clinical signs of chronic hypoxia in newborns with EIF were identified twice as common as in newborns without EIF (p=0.029). Moreover, none of the children had typical signs of Down syndrome while the number of preterm newborns was similar (p>0.05). Only newborns with EIF were diagnosed with different types of birth defects (7.94%) and generalized cytomegalovirus infection (1.46%). Hypoxic cardiopathy (that illustrates cardiovascular deadaptation) was 3.2 times more common in newborns with EIF (p=0.005). Conclusion: combination of EIF (2.67±0.9 mm) localized in the left or right ventricle and other sonographic signs, central nervous system defects and/or cardiovascular abnormalities require screening for perinatal infections as well as uterine and umbilical artery Doppler to minimize the risk of perinatal events. Keywords: perinatal period, echogenic intracardiac focus, newborns, perinatal losses, congenital anomaly, hypoxic cardiopathy, sonographic sign. For citation: Malinina E.I., Rychkova O.A., Chernysheva T.V. Markers of the pathological course of perinatal period in children with echogenic intracardiac focus. Russian Journal of Woman and Child Health. 2020;3(2):132-135. DOI: 10.32364/2618-8430-2020-3-2-132-135.